2017
DOI: 10.11114/bms.v3i4.2762
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Maturity in Companies in Terms of Strategic Directions: Cases of ONEE, ONEP and Barid Al Maghrib

Abstract: In an environm competitivene operations, thiThe present st drinking wate more in-depth approaches:-The compara -The recognizThe main obj different dime On the basis o group, classifi a group as typ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Türetken and Demirörs [16] demonstrated that organizational maturity is implemented through the efficient management of all the resources at all the stages of the organization by creating effective organizational management systems. Based on Mahir and Rajâa [17], the maturity aspect is commonly found in connection to the perspectives of organization success, the search of excellence by an organization, or strategic management. However, the focus towards research objects and elements largely differs.…”
Section: Introductionmentioning
confidence: 99%
“…Türetken and Demirörs [16] demonstrated that organizational maturity is implemented through the efficient management of all the resources at all the stages of the organization by creating effective organizational management systems. Based on Mahir and Rajâa [17], the maturity aspect is commonly found in connection to the perspectives of organization success, the search of excellence by an organization, or strategic management. However, the focus towards research objects and elements largely differs.…”
Section: Introductionmentioning
confidence: 99%